Biryani / Azlina Mohd Mydin and Elly Johana Johan - Mohd Mydin, Azlina (Unit Penerbitan e-Buletin JSKM, 2024)
Biryani is one of the well —known Indian cuisines that has its own devoted following. The meal stands out from the others thanks to its full spice, creamy sauces, and overall great flavour. one healthy dish that every Indian always enjoys is biryani. The precise origin of the dish Biryani Is explored in a Number of tales and variations. Most people think that the dish originated in Iraq, Iran or Persia. During the time of the Mughal Empire, biryani was introduced into Indian cuisine. in the, early going, not many people were aware of the dish. only during the accomplishments and Joyous occasions of royal families is this exquisite, fragrant, and detectable rice mixture available. Biryani didn’t become well-known or widely acclimated throughout the regions until much later, following are the some of the famous types of biryani in India.